Comprehensive assessment of the outcomes of inferior wall myocardial infarction according to echocardiography in patients after percutaneous coronary intervention - E. G. Akramova; A. A. Savelyev; R. Ya. Khamitova; E. V. Vlasova (Российский кардиологический журнал, 2023)
Aim. To identify significant echocardiographic parameters in the screening assessment of long-term outcomes of inferior wall myocardial infarction (MI) with primary percutaneous coronary intervention (PCI) using a logistic regression model.Material and methods. The study included the examination results of 144 people with inferior wall MI with primary PCI at admission, discharge and 6, 12, 24 months after discharge. Logistic regression analysis to identify screening outcomes of inferior wall MI included 184 variables, including 131 echocardiographic signs. Analysis of variance was performed using the ANOVA Type II method. The model quality was assessed using the likelihood ratio test and the Akaike criterion.Results. In patients with inferior wall MI and primary PCI, adverse outcomes were observed in 59,7% of cases in the form of repeated myocardial infarction and PCI, coronary artery bypass grafting, the development of stage 2 chronic heart failure, and/or rehospitalizations. For the long-term prognosis of inferior wall MI, in addition to left ventricular ejection fraction, mitral E/A, left atrial volume index and wall motion score index (WMSI), the following echocardiographic predictors were assessed: tricuspid S’ and e’, circumferential strain of the medial level, longitudinal strain of the apical and basal left ventricular levels, longitudinal strain of the segments included in the blood supply area of the circumflex artery.Conclusion. Echocardiographic parameters using Doppler and speckle-tracking technology have proven to be significant in screening outcomes of acute inferior wall MI with PCI.